2018
DOI: 10.1111/ppc.12267
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of injection site reaction and injection site pain of 1-month and 3-month long-acting injectable formulations of paliperidone palmitate

Abstract: Injection site reactions and pain were low and similar between both treatments, regardless of administration site and dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 12 publications
(19 reference statements)
1
25
0
Order By: Relevance
“…Low visual analog scale scores suggested mild injection-site pain and reduction from DB baseline to endpoint without notable differences between PP3M (Mean [SD]=19.5 [20.7] to 15.6 [17.9]) and PP1M (18.4 [20.4] to 15.5 [18.3]). Severity of injection-site induration, redness, and swelling were mild, with low frequency in both treatment groups, without any significant influence of the formulation difference 70. Overall, the safety profile of PP3M in the global patient population was consistent with findings in the East Asian, 71 European, and Latin American sub-groups, suggesting an absence of regional or ethnic influences.…”
Section: Efficacy and Outcomes For Pp3m Treatment In Schizophreniasupporting
confidence: 57%
“…Low visual analog scale scores suggested mild injection-site pain and reduction from DB baseline to endpoint without notable differences between PP3M (Mean [SD]=19.5 [20.7] to 15.6 [17.9]) and PP1M (18.4 [20.4] to 15.5 [18.3]). Severity of injection-site induration, redness, and swelling were mild, with low frequency in both treatment groups, without any significant influence of the formulation difference 70. Overall, the safety profile of PP3M in the global patient population was consistent with findings in the East Asian, 71 European, and Latin American sub-groups, suggesting an absence of regional or ethnic influences.…”
Section: Efficacy and Outcomes For Pp3m Treatment In Schizophreniasupporting
confidence: 57%
“… 11 , 17–27 Various injection site reactions for different LAI antipsychotics were reported in these studies, including pain, bleeding, and swelling. The most common injection site reaction was pain which was mainly reported in the studies by Hay, 17 Jones et al, 18 Atkins et al, 23 and Kern Sliwa et al 26 ( Table 2 ). The majority of the studies presented comparative data among different LAI antipsychotics.…”
Section: Resultsmentioning
confidence: 96%
“… 7 Atkins et al (2014) 23 Olanzapine 45–405 mg injection at 2-, 3- or 4-week intervals Pain was the most commonly reported, occurring in 2.9% of patients All other types of reactions occurred in <1% of patients Rates of discontinuation were low 8 Kisely et al (2015) 24 Fluphenazine q2w or q1M Paliperidone q1M Risperidone q2w Olanzapine q2w Haloperidol q1M Q2w injections were significantly less likely to lead to pain (RR=0.16, 95% CI=0.07–0.38; 2 studies n= 1667). Risperidone q2w was less likely to lead to site pain than q1M paliperidone (not statistically significant) 9 Chen et al (2016) 25 FGAPs Risperidone FGAPs showed lower injection pain severity compared to patients receiving risperidone LAI (VAS ratings), P<0.05 10 Misawa et al (2016) 11 Paliperidone Zuclopenthixol Risperidone Olanzapine Fluphenazine The prevalence of injection site reactions was not significantly different between the various antipsychotic formulations investigated 11 Kern Sliwa et al (2018) 26 Paliperidone q1M vs q3M Spontaneously-reported injection site pain for PP3M vs PP1M (3% vs 2%). Investigator-rated injection site reactions for PP3M vs PP1M: Induration (12% vs 10%), redness (10% vs 9%), swelling (7% vs 9%).…”
Section: Resultsmentioning
confidence: 98%
“…However, the sample size for the study comparing monthly versus two-monthly aripiprazole injections were small (n = 35 in each arm) (Risinger et al, 2017). The reasons for this are unclear, as injection site pain does not seem to be dependent on injection volume, dose, or site of administration (Atkins et al, 2014;Kern Sliwa et al, 2018). This may potentially be due to different injection techniques, although there is also the suggestion that the incidence of injection site pain reduces with an increasing number of injections received (Atkins et al, 2014).…”
Section: Discussionmentioning
confidence: 99%